Leishmanicidal activity of different parts from Arrabidaea brachypoda (DC.) Bureau (Bignoniaceae) - Pereira, Ivan de Oliveira [UNESP]; Rocha, Claudia Quintino da [UNESP]; Rosa, Isael Aparecido; Mendonça, Alexandre Tourino; Vilegas, Wagner [UNESP]; Sacramento, Luis Vitor Silva do [UNESP]; Marques, Marcos José (Universidade Vale do Rio Verde (UninCor), 2012)
Infections by protozoans of the genus Leishmania are the major worldwide health problem, with high endemicity in developing countries. The drugs of choice for the treatment of leishmaniasis are the pentavalent antimonials, which exert renal and cardiac toxicity. Thus, there is a strong need for safer and more effective treatments against leishmaniasis. The present study was designated to evaluate, by a bioguided assay, the leishmanicidal activity of hidro-ethanolic extracts from different parts (leves, caule and root) of one same plant the Arrabidaea brachypoda (DC.) Bureau. Its has been used to relieve general pain, painful joints and kidney stones in Brazilian folk medicine. Nevertheless, scientific information regarding this species is scarce; there are no reports related to its possible leishmanicidal activity. The leves extract presented the best activity on promastigotes forms of Leishmania (L.) amazonensis, when compared to the other extracts. It showed significant activity on Leishmania (L.) amazonensis. Our results are promising, showing that these compounds are biologically active on Leishmania (L.) amazonensis.
Keywords: Arrabidaea brachypoda; Leishmania; Promastigotes